DIABETES COMPLICATIONS AS DIABETES PATIENTS PREDICTORS OF REFERRAL - Nugroho Susanto; Yelli Yani Rusyani (Universitas Airlangga, 2022)
Background: Diabetes prevalence is growing faster in both developing and developed countries. Kidney failure, stroke, heart attack, leg amputation, and nerve damage are complications of diabetes caused by diabetes patients predictors of referral. Purpose: The study aims to describe diabetes complications as diabetes patients predictors of referral. Methods: The study design was used cross-sectional method. The population study is the participant with diabetes who have been treated in Public Health Care of Cangkringan from January 2018th until January 2019th. Samples were collected from total sampling who fulfilled the inclusion and exclusion criteria as complete medical records. The total sample was 414. Data of gender and age were collected from the medical record. Data of place was collected from GPS. Data of blood glucose level, complications and referral were collected from the medical record. Statistic test using chi-square and regression logistic. Results: Most diabetes patients were female, age > 55 years, diagnosis state long, distance ≤ 5 kilometres, no insulin-dependent, no complication, and no referral. Sex no significant differences PR = 0.91 (95% CI; 0.68-1.21), Age no significant different PR = 1.16 (95% CI; 0.88-1.51). Insulin significant different PR = 3.93 (95% CI: 3.17-4.88). Complication significant different PR = 3.53 (95% CI; 2.92-4.26). The main contributing to diabetes referral is a complication (β = 4.25; PR 71.20). Conclusion: The factors contributing to diabetes referral are insulin-dependent and complication, and the main factor contributing to diabetes referral is diabetes complication.